Basic characteristics of EEG epileptiform discharges triggered by lindane in a model of experimental prostatitis - Zubelić, Aleksa (Medicinski podmladak, 2022)
Introduction: Chronic prostatitis/Chronic Pelvic Pain Syndrome (CP/CPPS) is the most commonly diagnosed non-infectious prostatitis in urology. Studies have shown that CP/CPPS can induce neuroinflammation, which may result in CNS hyperexcitability and a tendency to develop epileptic seizures. Salvos of spikes are ictal EEG graph elements typical of the experimental model of lindane-induced epilepsy. There are a number of mathematical models for qualitative analysis of EEG, including the Fast Fourier Transform (FFT). It transforms the signal from time into the frequency domain, providing information on Power Spectral Densities (PSD). Aim: The aim of this study was to investigate the basic characteristics of epileptiform discharges induced by subconvulsive dose of lindane in rats, with experimentally induced CP/CPPS. Material and methods: CP/CPPS was induced by intraprostatic injection of 3% λ-carrageenan in male Wistar albino rats. Animals with CP/CPPS were implanted with EEG registration electrodes, on the seventh day after intraprostatic injection, lindane (L, 4 mg/kg, i.p., experimental group, CP/CPPS + L4, n = 6) or its solvent dimethyl-sulfoxide (DMSO, 2ml/kg, i.p., control group, CP/CPPS + DMSO, n = 6) was administered. An 8-channel EEG device was used in combination with software developed in the laboratory (NeuroSciLaBG). Ictal EEG epochs were extracted from the original signal and FFT analysis was performed to obtain information taking into account PSD in predefined frequency bands. Results: There was no ictal activity in the EEG of control animals. In experimental animals, ictal activity occurred and the mean duration of the ictal period was 2.06 s. FFT analysis revealed that the alpha frequency range (7-15 Hz) was markedly dominant during ictal activity. Conclusion: The results of this study showed the characteristics of epileptiform discharges in animals with experimentally induced CP/CPPS. This study and animal model are suitable for future translational studies of the comorbidities of this syndrome.